PTH-rP and PTH-R1 Expression in Placentas from Pregnancies Complicated by Gestational Diabetes: New Insights into the Pathophysiology of Hyperglycemia in Pregnancy - Angelo Sirico; Marco Dell’Aquila; Linda Tartaglione; Sascia Moresi; Giorgia Farì; Dario Pitocco; Vincenzo Arena; Antonio Lanzone (Diagnostics, 2021)
Background: this study investigated the expression of parathyroid hormone-related protein (PTH-rP) and PTH/PTH-rP receptor PTH-R1 in placentas from women with gestational DM (GDM), and the relationship between PTH-R1 and PTH-rP expression and pregnancy characteristics. Methods: we prospectively enrolled 78 pregnant women with GDM, and immunochemistry for PTH-rP and PTH-R1 was performed on placentas. Patients were grouped according to the positivity of PTH-R1 or PTH-rP expression, and pregnancy characteristics were compared between the two groups. Results: PTH-rP and PTH-R1 expression were highest in the extravillous cytotrophoblast and in the decidua. In extravillous cytotrophoblast, PTH-rP expression was higher in women with abnormal at fasting glycemia compared to women with abnormal 60′ or 120′ glycemia (25/25, 50% vs. 6/28, 21.4%, χ2 = 6.12, p = 0.01), and PTH-R1 expression was higher in women with abnormal oral glucose tolerance test (OGTT) at fasting glycemia compared to women with abnormal 60′ or 120′ glycemia (37/50, 74% vs. 15/28, 53.6%, χ2 = 3.37, p = 0.06). In syncytiotrophoblast, PTH-rP-positive placentas were characterized by higher incidence of 1 min Apgar score < 7 (2/9, 22.2% vs. 2/69, 2.9%, χ2 = 6.11, p = 0.01) and maternal obesity (4/9, 44.4% vs. 11/69, 16.7%, χ2 = 3.81, p = 0.05). Conclusion: placental PTH-rP and PTH-R1 expression is dependent on the type of maternal hyperglycemia, and it is associated with adverse pregnancy outcomes.